A PREDICTED APPROACH TOWARDS WOMEN IN ENGINEERING EDUCATION/PROFESSION USING MACHINE LEARNING TECHNIQUES - Tahira Mahboob (International Islamic University Islamabad, 2016)
Women have contributed to the diverse fields of engineering in modern and historical times. Women are often under-represented in the fields of engineering, both in academia and in the profession of engineering. A number of organizations and programs have been created to understand and overcome this tradition of gender disparity. In this paper we have applied a machine learning approach for the prediction of women in engineering in the coming future in Pakistan. We have identified several factors which influence the decision of women while selecting engineering as a profession.